ENVIRONMENTAL PAYOFF OF INTEGRATED WATERSHED MANAGEMENT PROGRAMME IN GARHWAL HIMALAYA- A CASE STUDY OF ORP FAKOT - Dhyani, B.L.; Samra, J.S.; Babu, Ram; Kumar, Nirmal (Journal of Soil and Water Conservation, 2022)
Development is a dynamic process and sensitive to various stimuli such as demographic pressure, programme and policies. Himalaya being highly sensitive to human interference, there are dangers of obvious ecological imbalances being set in motion in the region. Low productivity, rapid depletion of land and water resource, bio-diversity and environmental degradation are the consequences of past ill-coordinated gamut of developmental efforts. Participatory integrated watershed management programme approach demonstrated by Central Soil and Water Conservation Research and Training Institute, Dehradun in a 370 ha model watershed in Tehri Garhwal district of U P has resulted in change in land use pattern in favour of environmental improvement. Consequently runoff and soil loss from the watershed and decreased and agricultural output increased significantly. The study revealed that environmental payoff and economic returns from watershed management project at Fakot are attractive to lead to sustainable development in the area